Exploring English language teaching : language in action - Hall, Graham , 1969- (Routledge Introductions to applied linguistics, 2011)
Provides a single volume introduction to the field of ELT from an applied linguistics perspective. The book addresses four central themes within English language teaching: 'Classroom interaction and management'; 'Method, Postmethod and methodology'; 'Learners'; and the 'Institutional frameworks and social contexts' of ELT. For each, the book identifies key dilemmas and practices, examines how teachers and other language teaching professionals might intervene and deal with these concerns, and explores how such issues link to and inform applied linguistic theory. --from publisher description